2004
DOI: 10.1002/marc.200400185
|View full text |Cite
|
Sign up to set email alerts
|

On the β Transition in High Density Polyethylene: the Effect of Transcrystallinity

Abstract: Summary: Transcrystallinity in UHMWPE fiber‐reinforced HDPE composites promotes a significant β transition that is untypical of high‐density polyethylene. Surface profiling by atomic force microscopy identifies two distinct morphologies in the composite without a boundary phase between them, which coincide with the transcrystalline layer and with the bulk spherulitic matrix. As a result, the claim that attributes this transition to loose chain folds at the lamella surface is favored.Atomic force microscopy sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…It is well known that aramid fiber reinforced nylon 66 composites transcrystallize in such a way that a transcrystalline layer invades the whole space between the fibers and replaces most of the bulk crystallinity [23]. The amplification of the α′ peak can then be associated with the transcrystalline structure, similar to the β peak in HDPE [5]. Two examples of samples that exhibit an apparent α′ peak are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well known that aramid fiber reinforced nylon 66 composites transcrystallize in such a way that a transcrystalline layer invades the whole space between the fibers and replaces most of the bulk crystallinity [23]. The amplification of the α′ peak can then be associated with the transcrystalline structure, similar to the β peak in HDPE [5]. Two examples of samples that exhibit an apparent α′ peak are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 96%
“…An appropriate example from our own research is of high density polyethylene (HDPE), which in its pristine form exhibits a single second order transition, namely, T g . However, after undergoing a certain solid state crystallization stage, which results in crystalline restructuring, the same HDPE exhibits an untypically immense β transition in the amorphous phase [4,5]. In the present study we deal with yet another first order transition, namely the Brill transition in polyamides (e.g., nylon 66), for which a counterpart transition in the amorphous phase is explored.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior was also observed by Flores et al [17] It is suggested that this very gentle twist may be due to residual chain fold ordering at the fold surface, [12,13] perhaps due to a high concentration of loose folds at the lamellae surface as was found in ref. [4] We can compare our measured value of the pitch with values found for spherulitic PE [13] and with the value (12.68/mm) reported previously. [5,6] In that case, an epitaxial relationship between axially aligned orthorhombic crystals at the PE fiber surface and the crystalline lamellae in the TC layer was assumed as will be discussed below.…”
Section: Lamellar Twisting In the Pe Transcrystalline Layer: The Pitchmentioning
confidence: 82%
“…[16] Upon cooling, the fiber skin re-crystallizes to form an unoriented lamellar structure with evidence of cocrystallization with the matrix. [4] This last observation, as well as more recent X-ray diffraction data, [17] has put into question the validity of our previous premise that the epitaxial nucleation of the transcrystalline lamellae occurs such that their c-axes are aligned parallel to the axis of the fiber.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation